Corpus-based language comparison: From morphology to dependencies and beyond - Zeman, Daniel (Estudos Linguísticos (São Paulo. 1978), 2025)
We provide an overview of the Universal Dependencies multilingual corpus collection, its current status and numerous extensions, such as the UNER annotation of named entities or the CorefUD annotation of coreference and anaphora. We discuss the utility of the data in several areas of Digital Humanities, with a particular focus on comparative linguistics and typology. Keywords: annotated corpus; treebank; morphology; syntax; typology.